PENGARUH MEDIA PERMAINAN ULAR TANGGA TERHADAP HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR - Rohmania, Faridatur; Supratno, Haris; Siswanto, M. Bambang Edi (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
Based on the results of observations, it was found that sevral problems when learning took place, it was seen that learning activities tended to be possive due to the lack of selection of innovative learning strategies. The purpose of this study was to determine the effect of learning using the snake and ladder game media and conventional learning on the learning outcomes of grade III students at SDN Gongseng I Megaluh Jombang in academi year 2019/2020. This study was a pre-experimental design with an intact group comparison design. The population in this study were all students of class III SDN Gongseng I Megaluh, totaling 24 students. While the sample used is a full sample with 12 students as the control group and 12 students as the experimental group. Data collection through tests. The data analysis used was t-test analysis. The results of t-test analysis obtained tobs > ttab (4.39 > 2.17), so Ho was rejected and Ha was accepted. So it can be said that there is an influence on learning using the snake and ladder game media in grade III SDN Gongseng I Megaluh in the 2019/2020 scholl year. This defference can also be seen from the average acquisition of learning outcomes in the experimental group and the control group. The experimental group obtained a higher average value than the control group (81,6 > 60,8). This can prove that the use of the snake and ladder game media has a positive effect on the learning outcomes of grade III student at SDN Gongseng I Megaluh in academic year 2019/2020.